Early safety of tenofovir alafenamide in patients with a history of tubulopathy on tenofovir disoproxil fumarate: a randomized controlled clinical trial. Issue 3 (3rd November 2019) - Hamzah, L; Williams, D; Bailey, AC; Jones, R; Ibrahim, F; Musso, CG; Burling, K; Barbini, B; Campbell, L; Post, FA; ,
Abstract : Objectives: The aim of the study was to assess the effect of tenofovir alafenamide (TAF) on kidney and bone biomarkers in patients who developed proximal renal tubulopathy (PRT) while receiving tenofovir disoproxil fumarate (TDF). Methods: Individuals with a history of TDF‐associated PRT and currently suppressed HIV infection on a tenofovir‐sparing regimen were randomized 1:1 to continue current antiretroviral therapy or initiate emtricitabine (F)/TAF with discontinuation of nucleoside reverse transcriptase inhibitors (NRTIs) as appropriate. Renal and bone biomarkers were analysed at baseline, week 4 and week 12. The primary outcome was the mean difference between study arms in urine retinol‐binding protein:creatinine ratio (RBPCR) change from baseline to week 12. Data were analysed using linear regression, with robust standard errors (primary outcome), and repeated measures mixed effects models (secondary outcomes). The trial was registered under European Union Drug Regulating Authorities Clinical Trials Database 2016‐003345‐29. Results: We randomized 31 individuals [mean age 52.4 (standard deviation 0.3) years; 97% male; 90% white); all completed the study. At 12 weeks, there was no difference in change in RBPCR (β 19.6; 95% confidence interval −35.3, 74.5; P = 0.47), and no difference in change in estimated glomerular filtration rate (eGFR) (based on creatinine or cystatin C), albuminuria, proteinuria, renal phosphate or urea handling, (fasting) urine osmolality, parathyroid hormone and bone turnover markers in the control versus the F/TAF exposed groups. No cases of PRT were observed. Conclusions: In people with a history of proximal renal tubulopathy while on TDF, 12‐week exposure to TAF did not adversely affect renal tubular function. These data support continued evaluation of the long‐term safety of TAF in this group of patients.